C3-Alkylation of indoles and oxindoles by alcohols by means of borrowing hydrogen methodology. Issue 22 (28th May 2020) - Bartoccini, Francesca; Retini, Michele; Piersanti, Giovanni
Graphical abstract: Highlights: Borrowing hydrogen reaction of indoles and oxindoles with alcohols. Homogeneous and heterogeneous transition‐metal catalysts in CC bond-forming reactions. Methanol, aliphatic and heteroatom-functionalized alcohols as alkylating agents. Abstract: Transition metal‐catalyzed C3‐alkylation of indoles and oxindoles with nonderivatized alcohols, by means of borrowing hydrogen (BH) activation of the alcohol substrates, avoids the use of environmentally unfriendly alkylating agents. Only water is formed as the byproduct, thus making the BH process atom‐economical and environmentally benign. Diverse homogeneous and heterogeneous transition‐metal catalysts, indoles and oxindoles, and nonderivatized alcohols can be used for this transformation, hence rendering the BH process promising for replacing those procedures that use traditional alkylating agents. Although some earlier literature is discussed, this review mainly covers the literature published since 2015.